Natural abiotic iron-oxido-mediated formation of C1 and C2 compounds from environmentally important methyl-substituted substrates - Hädeler, Jonas; Velmurugan, Gunasekaran; Lauer, Rebekka; Radhamani, Rejith; Keppler, Frank; Comba, Peter (Journal of the American Chemical Society, 2023)
Organic and inorganic volatile compounds containing one carbon atom (C-1), such as carbon dioxide, methane, methanol, formaldehyde, carbon monoxide, and chloromethane, are ubiquitous in the environment, are key components in global carbon cycling, play an important role in atmospheric physics and chemistry, e.g., as greenhouse gases, destroy stratospheric and tropospheric ozone, and control the atmospheric oxidation capacity. Up to now, most C-1 compounds in the environment were associated with complex metabolic and enzymatic pathways in organisms or to combustion processes of organic matter. We now present compelling evidence that many C-1 and C-2 compounds have a common origin in methyl groups of methyl-substituted substrates that are cleaved by the iron oxide-mediated formation of methyl radicals. This scenario is derived from experiments with a mechanistically well-studied bispidine-iron-oxido complex as oxidant and dimethyl sulfoxide as the environmentally relevant model substrate and is supported by computational modeling based on density functional theory and ab initio quantum-chemical studies. The exhaustive experimental model studies, also involving extensive isotope labeling, are complemented with the substitution of the bispidine model system by environmentally relevant iron oxides and, finally, a collection of soils with varying iron and organic matter contents. The combination of all data suggests that the iron oxide-mediated formation of methyl radicals from methyl-substituted substrates is a common abiotic source for widespread C-1 and C-2 compounds in the environment.
Im Titel ist die Ziffer 1 bei C1 und die Ziffer 2 bei C2 jeweils tiefgestellt
Gesehen am 23.01.2024